Peran Financial Distress, Persistensi Laba dan Earning Pressure terhadap Konservatisme Akuntansi : Bukti Empiris Sektor Keuangan di Indonesia - Zella Arfi Andiny; Agung Prayogi (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to examine the effect of financial distress, earnings persistence, and earning pressure on accounting conservatism in financial sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employs secondary data obtained from companies’ annual financial statements, resulting in a total of 88 firm-year observations. The analytical method used is panel data regression with a common effect model approach. The results indicate that financial distress has a positive and significant effect on accounting conservatism, suggesting that firms experiencing higher levels of financial difficulty tend to adopt more conservative accounting practices. In contrast, earnings persistence has a negative and significant effect on accounting conservatism, implying that firms with more stable earnings are less likely to apply higher levels of conservatism. Meanwhile, earning pressure does not have a significant effect on accounting conservatism. These findings highlight that a firm’s financial condition and earnings characteristics play an important role in determining the level of accounting conservatism. The results provide practical implications for management in formulating accounting policies that consider the firm’s financial condition, as well as for investors and regulators in assessing the quality of financial reporting